Tax avoidance, board diversity and management fraud: Malaysian public listed companies / Roshidah Safeei - Safeei, Roshidah (2023)
In light of recent high-profile business failures, such as Enron, WorldCom, and Toshiba, investors have become more cognizant of the possibility that a company’s financial statements may not accurately reflect its performance due to management fraud. The purpose of this study is threefold: to investigate the influence of tax avoidance on management fraud occurrence, to investigate the influence of board diversity on management fraud occurrence and to examine the moderating effects of board diversity on the relationship between tax avoidance and management fraud occurrence in Malaysian public listed companies. Using enforcement action releases issued by the Security Commission of Malaysia and Bursa Malaysia, this study identifies 50 fraud firms that committed management fraud from 2012 to 2019. The fraud firms are matched with non-fraud firms using a one-to-two ratio based on the same industry, year and firm size. As a result, this study utilises a sample of 50 fraud and 100 non-fraud firms listed on Bursa Malaysia This study employs binary logistic regression analysis and finds that tax avoidance is negatively associated with management fraud, as fraud firms are less likely to engage in tax avoidance activities. Furthermore, this study finds a significant relationship between board tenure and board education diversity with management fraud whereby an increase in board tenure and board education diversity decreases the likelihood of the occurrence of management fraud. The study also finds that board tenure and education diversity moderate the relationship between tax avoidance and management fraud. However, no evidence is found to suggest that board gender or age diversity has a mitigating effect. The results of this study indicate that board tenure and board education diversity play a significant role in curbing management fraud in Malaysian firms. Overall, this study provides valuable insights into the relationships between tax avoidance, board diversity, and management fraud in Malaysian firms, an area that has been understudied in the past.